2014
DOI: 10.1038/jcbfm.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Amyloid PET in Cerebral Amyloid Angiopathy-Related Symptomatic Intracerebral Hemorrhage

Abstract: By detecting β-amyloid ( Aβ) in the wall of cortical arterioles, amyloid positron emission tomography (PET) imaging might help diagnose cerebral amyloid angiopathy (CAA) in patients with lobar intracerebral hemorrhage (I-ICH). No previous study has directly assessed the diagnostic value of 11-Pittsburgh compound B (PiB) PET in probable CAA-related I-ICH against healthy controls (HCs). 11C-PiB-PET and magnetic resonance imaging (MRI) including T2* were obtained in 11 nondemented patients fulfilling the Boston c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 42 publications
6
84
1
Order By: Relevance
“…21 One previous study found that 4 out of 9 cognitively healthy older controls had high PiB retention, the highest reported rate of false positivity in amyloid imaging field but the sensitivity to detect CAA was still excellent (91%) in this particular study. 38 It is plausible that the high specificity that we found might suffer in patients 80 and older due to increased incidence of asymptomatic amyloid positivity. Our data nevertheless suggest that a negative florbetapir scan might be used to exclude a diagnosis of severe CAA, providing valuable guidance to the management of patients with isolated lobar ICH, mixed location ICH, and cerebellar ICH, and patients who cannot undergo MRI.…”
Section: Resultsmentioning
confidence: 83%
“…21 One previous study found that 4 out of 9 cognitively healthy older controls had high PiB retention, the highest reported rate of false positivity in amyloid imaging field but the sensitivity to detect CAA was still excellent (91%) in this particular study. 38 It is plausible that the high specificity that we found might suffer in patients 80 and older due to increased incidence of asymptomatic amyloid positivity. Our data nevertheless suggest that a negative florbetapir scan might be used to exclude a diagnosis of severe CAA, providing valuable guidance to the management of patients with isolated lobar ICH, mixed location ICH, and cerebellar ICH, and patients who cannot undergo MRI.…”
Section: Resultsmentioning
confidence: 83%
“…1,3,29 On the other hand, several attempts using amyloid imaging, such as 11 C-Pittsburgh compound B positron emission tomography ( 11 C-PiB PET), have been made to detect CAA as an underlying disease in several pathological conditions such as dementia, cortical SAH, and cerebral angitis. [30][31][32][33][34] A positive relationship between local amyloid burden and a future risk for hemorrhage has been suggested based on the result of a longitudinal cohort study with 11 C-PiB PET and MRI. 31 However, the presence of vascular amyloid in the tissue sample is not perfectly specific for CAA-ICH because elderly people may incidentally present with asymptomatic vascular amyloid deposition.…”
Section: Factors That Influence the Detection Of Caa Pathologymentioning
confidence: 99%
“…4 The protocol was approved by the Cambridgeshire Ethics Committee, and all subjects gave informed consent.…”
Section: Study Subjectsmentioning
confidence: 99%
“…4 On the same day as the PiB-PET, each subject underwent 3T MRI (slice thickness, 4 mm; slice gap, 5 mm), including T2-weighted, T1-weighted magnetization-prepared rapid gradient-echo, fluid-attenuated inversion recovery, and gradient-recalled echo, using standard T2* sequences. MRIs were reviewed blinded to clinical and PET data.…”
mentioning
confidence: 99%